This action might not be possible to undo. Are you sure you want to continue?

BooksAudiobooksComicsSheet Music### Categories

### Categories

### Categories

### Publishers

Scribd Selects Books

Hand-picked favorites from

our editors

our editors

Scribd Selects Audiobooks

Hand-picked favorites from

our editors

our editors

Scribd Selects Comics

Hand-picked favorites from

our editors

our editors

Scribd Selects Sheet Music

Hand-picked favorites from

our editors

our editors

Top Books

What's trending, bestsellers,

award-winners & more

award-winners & more

Top Audiobooks

What's trending, bestsellers,

award-winners & more

award-winners & more

Top Comics

What's trending, bestsellers,

award-winners & more

award-winners & more

Top Sheet Music

What's trending, bestsellers,

award-winners & more

award-winners & more

P. 1

Fourier Series|Views: 28|Likes: 0

Published by sert_as

See more

See less

https://www.scribd.com/doc/53156025/Fourier-Series

04/16/2011

text

original

John Appleby

Contents

1 Important Facts 1

2 Exercises and Examples 2

1 Important Facts

1. Suppose f(x) is a periodic function of period 2π which can be represented

by a TRIGONOMETRIC FOURIER SERIES

f(x) = a

0

+

∞

¸

n=1

a

n

cos nx + b

n

sin nx.

(This means that the series above converges to f(x).)

Then the Fourier Coeﬃcients satisfy the Euler Formulae, namely:

a

0

=

1

2π

π

−π

f(x) dx

a

n

=

1

π

π

−π

f(x) cos nxdx for n = 1, 2, . . .

b

n

=

1

π

π

−π

f(x) sin nxdx for n = 1, 2, . . .

2. A function f is said to be even if

f(−x) = f(x) for all x ∈ R

and odd if

f(−x) = −f(x) for all x ∈ R

Recall the product of two even functions is even, the product of two odd func-

tions is even and the product of an even and an odd function is odd. Compare

2

the multiplication of even and odd functions to the addition of even and

odd integers.

3. If f is an odd function then

π

−π

f(x) dx = 0,

while if f is an even function, then

π

−π

f(x) dx = 2

π

0

f(x) dx

2 Exercises and Examples

Example 1. Let f be a periodic function of period 2π such that

f(x) = π

2

−x

2

for x ∈ (−π, π).

Supposing that f has a convergent trigonometric Fourier series, show that

π

2

−x

2

=

2π

2

3

+

∞

¸

n=1

−4

n

2

(−1)

n

cos nx. (2.1)

SOLUTION: The solution can be eﬀected in a number of separate steps:

• Check whether f is even or odd.

• If f is odd, all the Fourier coeﬃcients a

n

for n = 0, 1, 2 . . . are zero; if f

is even, all the Fourier coeﬃcients b

n

for n = 1, 2 . . . are zero.

• Compute the remaining Fourier coeﬃcients using the Euler Formulae. It

is generally a good strategy to use Integration by Parts, successively

integrating sin nx and cos nx and diﬀerentiating f(x).

• Replace the expressions for the Fourier coeﬃcients a

n

, b

n

in

f(x) = a

0

+

∞

¸

n=1

a

n

cos nx + b

n

sin nx.

STEP 1: f(−x) = π

2

−(−x)

2

= π

2

−x

2

= f(x) so f is even.

STEP 2: Since f(x) is even and sin nx is odd, f(x) sin nx is odd and hence

b

n

=

1

π

π

−π

f(x) cos nxdx = 0.

Calculus of Several Variables and Fourier Analysis(MS224) c John Appleby, 2001

3

STEP 3: Since f(x) is even and cos nx is even, f(x) cos nx is even, and so

π

−π

f(x) cos nxdx = 2

π

0

f(x) cos nxdx.

Therefore,

a

n

=

1

π

π

−π

f(x) cos nxdx =

1

π

2

π

0

f(x) cos nxdx =

2

π

π

0

(π

2

−x

2

) cos nx

(2.2)

As suggested above, we calculate the integral in (2.2) by Integration by Parts.

Recall the Integration by Parts formula:

b

a

f(x)g

(x) dx = f(x)g(x)

b

x=a

−

b

a

f

(x)g(x) dx (2.3)

Let

f(x) = π

2

−x

2

and g

(x) = cos nx

so

f

(x) = −2x and g(x) =

cos nxdx =

1

n

sin nx.

Using (2.3) and the above, we have

π

0

(π

2

−x

2

)

. .. .

f

cos nx

. .. .

g

dx (2.4)

= (π

2

−x

2

)

. .. .

f

1

n

sin nx

. .. .

g

π

0

−

π

0

−2x

....

f

1

n

sin nx

. .. .

g

dx

= (π

2

−π

2

)

1

n

sin nπ −(π

2

−0

2

)

1

n

sin 0 +

2

n

π

0

xsin nxdx

=

2

n

π

0

xsin nxdx. (2.5)

Now we calculate this last integral using integration by parts: let

f(x) = x and g

(x) = sin nx,

so

f

(x) = 1 and g(x) =

sin nxdx =

−cos nx

n

.

Using (2.3), and remembering that cos nπ = (−1)

n

, sin nπ = 0 for n an integer,

we have

π

0

x

....

f

sin nx

. .. .

g

dx = x

....

f

−cos nx

n

. .. .

g

π

0

−

π

0

1

....

f

−cos nx

n

. .. .

g

dx

= π

−cos nπ

n

−0

−cos 0

n

+

1

n

π

0

cos nxdx

= −

1

n

π(−1)

n

+

1

n

sin nx

n

π

0

= −

1

n

π(−1)

n

.

Calculus of Several Variables and Fourier Analysis(MS224) c John Appleby, 2001

4

Using (2.2), (2.5) and the above, we have

a

n

=

2

π

π

0

(π

2

−x

2

) cos nxdx =

2

π

2

n

π

0

xcos nxdx

=

2

π

2

n

−

1

n

π(−1)

n

=

−4

n

2

(−1)

n

.

It remains to calculate a

0

, which is given by

a

0

=

1

2π

π

−π

f(x) dx =

1

2π

2

π

0

π

2

−x

2

dx

=

1

π

π

2

x −

x

3

3

π

0

=

1

π

π

3

−

π

3

3

=

2π

3

3

where we use the fact that f(x) = π

2

−x

2

is even.

STEP 4: Using the formulae obtained above for the Fourier coeﬃcients, we

have

π

2

−x

2

=

2π

3

3

+

∞

¸

n=1

−4

n

2

(−1)

n

cos nx + 0. sin nx =

2π

3

3

+

∞

¸

n=1

−4

n

2

(−1)

n

cos nx

Example 2. Show that the trigonometric Fourier series of f(x) = 3x for x ∈

(−π, π) is given by

∞

¸

n=1

−6

n

(−1)

n

sin nx.

SOLUTION:

STEP 1: f(−x) = 3. −x = −3x = −f(x), so f is an odd function.

STEP 2: Since f(x) is odd and cos nx is even, it follows that f(x) cos nx is

odd, so

a

n

=

1

π

π

−π

f(x) cos nxdx =

1

π

.0 = 0.

Moreover, since f is odd

a

0

=

1

2π

π

−π

f(x) dx =

1

2π

.0 = 0.

STEP 3: We need to calculate the Fourier coeﬃcients using the Euler Formulae.

However, noting that f(x) and sin nx are odd, and therefore that f(x) sin nx is

even we have

b

n

=

1

π

π

−π

f(x) sin nxdx =

1

π

2

π

0

f(x) sin nxdx =

6

π

π

0

xcos nxdx. (2.6)

The latter integral is calculated using integration by parts.

Calculus of Several Variables and Fourier Analysis(MS224) c John Appleby, 2001

5

Exercise 2.1. Show that

π

0

xsin nxdx = x

−cos nx

n

π

0

−

π

0

−cos nx

n

dx =

−π

n

(−1)

n

.

By virtue of Exercise 2.1, we have, from (2.6)

b

n

=

6

π

−π

n

(−1)

n

= −

6

n

(−1)

n

.

STEP 4: The Fourier series of f(x) = 3x is given by

a

0

+

∞

¸

n=1

a

n

cos nx + b

n

sin nx = 0 +

∞

¸

n=1

0 cos nx +−

6

n

(−1)

n

sin nx

=

∞

¸

n=1

−

6

n

(−1)

n

sin nx.

Now try the following

Exercise 2.2.

(i) Show that x

3

cos nx is an odd function and x

3

sin nx is an even function.

Hence give the value of

π

−π

x

3

cos nxdx

and write down another expression equal to

π

−π

x

3

sin nxdx.

(ii) By integrating by parts, show that

π

0

x

3

sin nxdx = −

(−1)

n

π

3

n

+

3

n

π

0

x

2

cos nxdx.

Hint: Recall for integer values of n that cos nπ = (−1)

n

.

(iii) Given that

π

0

x

2

cos nxdx = −

2

n

π

0

xsin nxdx

and

π

0

xsin nxdx = −

π

n

(−1)

n

,

use part (ii) to prove that

π

0

x

3

sin nxdx =

6π

n

3

(−1)

n

−

π

3

n

(−1)

n

.

(iv) Using parts (i) and (iii), and supposing that the Fourier series converges,

show for all x ∈ (−π, π) that

x

3

=

∞

¸

n=1

2(−1)

n

6

n

3

−

π

2

n

sin nx.

Calculus of Several Variables and Fourier Analysis(MS224) c John Appleby, 2001

• Replace the expressions for the Fourier coeﬃcients an . are zero. Supposing that f has a convergent trigonometric Fourier series. bn in ∞ f (x) = a0 + n=1 an cos nx + bn sin nx. Let f be a periodic function of period 2π such that f (x) = π 2 − x2 for x ∈ (−π.1) SOLUTION: The solution can be eﬀected in a number of separate steps: • Check whether f is even or odd. 1. all the Fourier coeﬃcients an for n = 0. 2 .2 the multiplication of even and odd functions to the addition of even and odd integers. −π Calculus of Several Variables and Fourier Analysis(MS224) c John Appleby. then π π f (x) dx = 2 −π 0 f (x) dx 2 Exercises and Examples Example 1. f (x) sin nx is odd and hence bn = 1 π π f (x) cos nx dx = 0. if f is even. π). 2 . STEP 2: Since f (x) is even and sin nx is odd. 3 n2 n=1 ∞ (2. • Compute the remaining Fourier coeﬃcients using the Euler Formulae. . successively integrating sin nx and cos nx and diﬀerentiating f (x). It is generally a good strategy to use Integration by Parts. . show that π 2 − x2 = −4 2π 2 + (−1)n cos nx. . −π while if f is an even function. If f is an odd function then π f (x) dx = 0. . 3. • If f is odd. are zero. 2001 . all the Fourier coeﬃcients bn for n = 1. STEP 1: f (−x) = π 2 − (−x)2 = π 2 − x2 = f (x) so f is even.

2) by Integration by Parts. we have π (π 2 − x2 ) cos nx dx 0 (2. Recall the Integration by Parts formula: b b b f (x)g (x) dx = f (x)g(x) a x=a − a f (x)g(x) dx (2. so f (x) = 1 and g(x) = sin nx dx = − cos nx . we calculate the integral in (2. n 0 (2. we have π 0 x sin nx dx = f g π − cos nx − cos nx π − 1 dx n n 0 0 f f g g − cos nπ − cos 0 1 π = π −0 + cos nx dx n n n 0 1 1 sin nx π 1 = − π(−1)n .5) Now we calculate this last integral using integration by parts: let f (x) = x and g (x) = sin nx. Therefore.3) and the above.2) As suggested above. and so π π f (x) cos nx dx = 2 −π 0 f (x) cos nx dx. an = 1 π π f (x) cos nx dx = −π 1 2 π π f (x) cos nx dx = 0 2 π π (π 2 − x2 ) cos nx 0 (2. 2001 .3 STEP 3: Since f (x) is even and cos nx is even.3) Let f (x) = π 2 − x2 so f (x) = −2x and g(x) = cos nx dx = and g (x) = cos nx 1 sin nx. f (x) cos nx is even.4) f = (π 2 − x2 ) g π π 1 1 sin nx − −2x sin nx dx n n 0 0 f f g g 1 1 2 π x sin nx dx = (π 2 − π 2 ) sin nπ − (π 2 − 02 ) sin 0 + n n n 0 2 π = x sin nx dx. sin nπ = 0 for n an integer.3). n Using (2. and remembering that cos nπ = (−1)n . n Using (2. = − π(−1)n + n n n 0 n x Calculus of Several Variables and Fourier Analysis(MS224) c John Appleby.

πn n n π x cos nx dx 0 It remains to calculate a0 . n n=1 SOLUTION: STEP 1: f (−x) = 3. we have an = 2 π 2 22 (π − x2 ) cos nx dx = π 0 πn 22 1 −4 = − π(−1)n = 2 (−1)n .4 Using (2. so f is an odd function. (2.0 = 0. However. (2. STEP 4: Using the formulae obtained above for the Fourier coeﬃcients. Show that the trigonometric Fourier series of f (x) = 3x for x ∈ (−π. π −π π Moreover. since f is odd a0 = 1 2π π f (x) dx = −π 1 .5) and the above. so 1 π 1 an = f (x) cos nx dx = . we have −4 2π 3 −4 2π 3 + (−1)n cos nx + 0.6) 0 The latter integral is calculated using integration by parts. and therefore that f (x) sin nx is even we have bn = 1 π π f (x) sin nx dx = −π 1 2 π π f (x) sin nx dx = 0 6 π π x cos nx dx.0 = 0. π) is given by ∞ −6 (−1)n sin nx.2). which is given by a0 = = 1 2π 1 π π f (x) dx = −π 1 2 2π = 1 π π π 2 − x2 dx 0 π2 x − x3 3 π 0 π3 − π3 3 = 2π 3 3 where we use the fact that f (x) = π 2 − x2 is even. − x = −3x = −f (x). 2π STEP 3: We need to calculate the Fourier coeﬃcients using the Euler Formulae. Calculus of Several Variables and Fourier Analysis(MS224) c John Appleby. sin nx = + (−1)n cos nx π −x = 3 n2 3 n2 n=1 n=1 2 2 ∞ ∞ Example 2. it follows that f (x) cos nx is odd. STEP 2: Since f (x) is odd and cos nx is even. noting that f (x) and sin nx are odd. 2001 .

Hence give the value of π x3 cos nx dx −π and write down another expression equal to π x3 sin nx dx. −π (ii) By integrating by parts. 0 Hint: Recall for integer values of n that cos nπ = (−1)n .5 Exercise 2. we have. n 6π π3 (−1)n − (−1)n . n3 n use part (ii) to prove that π x3 sin nx dx = 0 (iv) Using parts (i) and (iii). Show that π x sin nx dx = x 0 − cos nx n π π − 0 0 −π − cos nx dx = (−1)n .1. (iii) Given that 0 π x2 cos nx dx = − and 0 π 2 n π x sin nx dx 0 π x sin nx dx = − (−1)n . show that π x3 sin nx dx = − 0 (−1)n π 3 3 + n n π x2 cos nx dx.1. n n By virtue of Exercise 2. 2001 . (i) Show that x3 cos nx is an odd function and x3 sin nx is an even function. show for all x ∈ (−π. π n n STEP 4: The Fourier series of f (x) = 3x is given by bn = ∞ a0 + n=1 an cos nx + bn sin nx = = 0+ ∞ 6 0 cos nx + − (−1)n sin nx n n=1 ∞ 6 − (−1)n sin nx.2. from (2. Calculus of Several Variables and Fourier Analysis(MS224) c John Appleby. π) that ∞ x3 = n=1 2(−1)n 6 π2 − 3 n n sin nx.6) 6 −π 6 (−1)n = − (−1)n . n n=1 Now try the following Exercise 2. and supposing that the Fourier series converges.

8086 Handouts

Gibss Fourier Series

AXE-MML-msc

DHCP

Cisco Lab Troubleshoot Static Routes

Web Browsing Sequence Diagram

GSM_Location_Update_Sequence_Diagram

GSM Originating Call Flow

- Read and print without ads
- Download to keep your version
- Edit, email or read offline

Are you sure?

This action might not be possible to undo. Are you sure you want to continue?

CANCEL

OK

You've been reading!

NO, THANKS

OK

scribd

/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->